γ-Irradiated Chitosan From Carcinoscorpius rotundicauda (Latreille, 1802) Improves the Shelf Life of Refrigerated Aquatic Products - Pati, Siddhartha; Sarkar, Tanmay; Sheikh, Hassan I.; Bharadwaj, Kaushik Kumar; Mohapatra, Pranab Kishor; Chatterji, Anil; Dash, Bisnu Prasad; Edinur, Hisham Atan; Nelson, Bryan Raveen (Frontiers in Marine Science, 2021)
The γ-irradiated horseshoe crab chitosan was used as food coating to extend the shelf life of marine shrimp and fish. Fourier-transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FE-SEM), and X-ray diffraction (XRD) were used to characterize the γ-irradiated chitosan. After employing control (untreated seafood samples/no preservatives), chemical preservation (treated with 2% glacial acetic acid) and 2% chitosan (0, 10, and 20 kGy γ-irradiation) for the assessment assay, the shrimp (Penaeus merguiensis), pomfret (Pampus argenteus), and hilsa fish (Tenualosa ilisha) samples were examined for pH, thiobarbituric acid reactive substance (TBARS), total viable counts (TVC), and sensory evaluation changes while under 15-day refrigeration at 4°C. The results of FT-IR, XRD, and FE-SEM analysis revealed that irradiated chitosan possessed a crystalline structure with smooth texture on its surface. Analysis of pH, TBARS, TVC, and sensory evaluation demarcated irradiated chitosan with the ability to delay microbial growth and this prolonged the shelf life of refrigerated shrimp and fish. With novelty on γ-irradiated horseshoe crab chitosan use as natural preserving agent, fisheries industries and food packaging practitioners would benefit from its microbial-inert abilities particularly for long distant cold storage transport of packaged marine meats.